Spatial representation from gene to mind - Landau, Barbara, 1949-; Hoffman, James E. (New York ; Oxford : Oxford University Press, 2012)
Despite our impression of a seamless spatial world, mature human spatial knowledge is composed of sub-systems, each specialized. This book uses the case of Williams syndrome to argue for specialization of function in both normal and unusual development. The evidence suggests a speculative hypothesis linking the genetic deficit to changes in the timing of emergence for different sub-systems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Williams syndrome; Cognition disorders